2018
DOI: 10.1186/s12906-018-2180-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera consumption on diabetic rats

Abstract: BackgroundTherapeutic use of leaves of M. oleifera has been evaluated in diabetes because of its possible capacity to decrease blood glucose and lipids concentration after ingestion, as result of the polyphenols content and others compounds. Nevertheless most results have been obtain from leaf extract, therefore this study would use leaf powder as the regular way of consumption of population to know effects over toxicity glucose, triglycerides, cholesterol, corporal weight, and predominant groups of microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 38 publications
(48 reference statements)
5
51
0
12
Order By: Relevance
“…In another study, consumption of moringa leaf powder at 50 mg/day by alloxan‐induced diabetic rats for 8 weeks showed a significant decrease in blood glucose concentration compared with untreated diabetic rats (Villarruel‐Lopez et al, ). In the same study, different doses of moringa leaves (100, 250, and 500 mg/kg) showed no adverse effects (e.g., possible change in food intake, diarrhea, decreased activity, unusual body growth, bleeding, or death) in the rats; in addition, no prominent changes were found in genotoxicity parameters (Villarruel‐Lopez et al, ). Similarly, treatment with ethanolic extract of moringa leaves at a dose of 150 mg kg −1 day −1 for 5 weeks significantly decreased fasting blood glucose level from 483 to 312 mg/dl in Type 2 diabetic mice compared with control group (Tang et al, ).…”
Section: Animal Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study, consumption of moringa leaf powder at 50 mg/day by alloxan‐induced diabetic rats for 8 weeks showed a significant decrease in blood glucose concentration compared with untreated diabetic rats (Villarruel‐Lopez et al, ). In the same study, different doses of moringa leaves (100, 250, and 500 mg/kg) showed no adverse effects (e.g., possible change in food intake, diarrhea, decreased activity, unusual body growth, bleeding, or death) in the rats; in addition, no prominent changes were found in genotoxicity parameters (Villarruel‐Lopez et al, ). Similarly, treatment with ethanolic extract of moringa leaves at a dose of 150 mg kg −1 day −1 for 5 weeks significantly decreased fasting blood glucose level from 483 to 312 mg/dl in Type 2 diabetic mice compared with control group (Tang et al, ).…”
Section: Animal Studiesmentioning
confidence: 96%
“…In a recent study, administration of ethyl acetate extract of moringa leaves at a dose of 200 mg/kg to streptozotocin (STZ)-induced diabetic rats for 30 days significantly decreased their blood glucose and glycosylated hemoglobin (HbA1c) levels compared with control group (Bamagous et al, 2018). In another study, consumption of moringa leaf powder at 50 mg/day by alloxan-induced diabetic rats for 8 weeks showed a significant decrease in blood glucose concentration compared with untreated diabetic rats (Villarruel-Lopez et al, 2018). In the same study, different doses of moringa leaves (100, 250, and 500 mg/kg) showed no adverse effects (e.g., possible change in food intake, diarrhea, decreased activity, unusual body growth, bleeding, or death) in the rats; in addition, no prominent changes were found in genotoxicity parameters (Villarruel-Lopez et al, 2018).…”
Section: Animal Studiesmentioning
confidence: 98%
“…It contains large amounts of various phytochemicals including phenolics, tannins, saponin, glucosinolates, flavonoids, flavonol glycosides, quercetin, kaempferol, phytate, and lectins (Maizuwo et al, 2017;Atta et al, 2017;. These phytochemicals help in treating various diseases as antidiarrheal, antiulcerative, and hepato-and nephroprotective, antidiabetic and anticancer effects (Gopalakrishnan et al, 2016;Shalaby et al, 2016;Atta et al, 2017Atta et al, , 2018Villarruel-López et al, 2018;Hagoel et al, 2019). All parts of MO tree are edible.…”
mentioning
confidence: 99%
“…Also A. Villarruel-López et al, 2018 reported that the beneficial effects of moringa leaves are due to its polyphenols content and others useful compounds, 6 .…”
Section: Bar Charts Showing Estimated Mean Values Of Comet Assay For mentioning
confidence: 99%
“…Moringa oleifera (MO) "drum stick tree" belongs to the Moringaceae family. This tree is essential because it has medicinal uses for its flowers, pods and leaves, 6 . Moringa leaf is a prospective source of natural antioxidants such as total phenolics and antioxidant vitamins A, C and E, polyphenol oxidase, ascorbic acid oxidase, and catalase, 7 .…”
Section: Introductionmentioning
confidence: 99%